Bridging the transport pathway of charge carriers in a Ta3N5 nanotube array photoanode for solar water splitting. Issue 31 (10th June 2015) - Zhang, Peng; Wang, Tuo; Zhang, Jijie; Chang, Xiaoxia; Gong, Jinlong
Abstract : This paper describes an approach to synthesize a tightly adhered Ta3 N5 nanotube array (NTA) photoanode with enhanced electron conductivity between the Ta3 N5 layer and the substrate via a two-step anodization method. Abstract : This paper describes an approach to synthesize a tightly adhered Ta3 N5 nanotube array (NTA) photoanode with enhanced electron conductivity between the Ta3 N5 layer and the substrate via a two-step anodization method. The obtained tightly adhered Ta3 N5 NTA photoanode exhibits excellent photoelectrochemical properties with an optimal photocurrent up to 5.3 mA cm −2 at 1.6 V vs. the reversible hydrogen electrode. This approach provides an effective strategy to address the adhesion issue of one dimensional semiconductor photoanodes.